Radiatively Active Clouds and Magnetic Effects Explored in a Grid of Hot Jupiter GCMs - Thomas D. Kennedy; Emily Rauscher; Isaac Malsky; Michael T. Roman; Hayley Beltz (The Astrophysical Journal)
Cloud formation and magnetic effects are both expected to significantly impact the structures and observable properties of hot Jupiter atmospheres. For some hot Jupiters, thermal ionization and condensation can coexist in a single atmosphere, and both processes are important. We present a grid of general circulation models across a wide range of irradiation temperatures with and without incorporating the effects of magnetism and cloud formation to investigate how these processes work in tandem. We find that clouds are present in the atmosphere at all modeled irradiation temperatures, while magnetic effects are negligible for planets with irradiation temperatures cooler than 2000 K. At and above this threshold, clouds and magnetic fields shape atmospheres together, with mutual feedback. Models that include magnetism, through their influence on the temperature structure, produce more longitudinally symmetric dayside cloud coverage and more equatorially concentrated clouds on the nightside and morning terminator. To indicate how these processes would affect observables, we generate bolometric thermal and reflected phase curves from these models. The combination of clouds and magnetic effects increases thermal phase-curve amplitudes and decreases peak offsets more than either process does individually.